COMPENSATOR OF UNSTATIONARY TEMPORAL ERRORS OF THE WIDE BAR MEASURING CHANNELS WIDE BAR - Rudyk, Vadym; Gonchar, Serhiy (Scientific Works of Vinnytsia National Technical University, 2011)
The paper considers the question of an approach to determination of unstationary temporal errors, nature of their origin, the analysis of errors by an analytical method using the models of the measuring channels. There had been given the mathematical correlations which can be used for determination of the indicated errors, and also graphs which evidently demonstrate the conduct of such errors at the different values of parameters of channel and signal,. The algorithm of the signal processing is considered with the purpose of indemnification of unstationary temporal error in the measuring channels wide bar and realization of this algorithm in a vehicle kind.